2008
DOI: 10.1080/13651820802140737
|View full text |Cite
|
Sign up to set email alerts
|

Conservative approach in the management of severe acute pancreatitis: eight-year experience in a single institution

Abstract: The conservative protocol-based approach is a rational treatment strategy for the management of SAP and can be successfully implemented in the setting of the university hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
4
10
0
Order By: Relevance
“…This was comparable to the study by Pupelis G et al 6 In the other studies gall stone was the main etiological factor. The percentage of idiopathic cases was comparable.…”
Section: Figure 12supporting
confidence: 92%
“…This was comparable to the study by Pupelis G et al 6 In the other studies gall stone was the main etiological factor. The percentage of idiopathic cases was comparable.…”
Section: Figure 12supporting
confidence: 92%
“…Table 3 shows the three main aetiologies of acute pancreatitis (alcohol, gallstone and other or idiopathic aetiology) reported from studies across Europe. Of 11 studies from eastern Europe, seven (64%) had a higher ratio of alcohol to gallstone aetiologies [10,[24][25][26][27][28]77], which is significantly higher than for two of 16 studies from southern Europe (13%; p=0.012) [8,30], and for three of 21 studies from northern Europe (14%; p=0.013) [29,31], although not significantly different to three of nine studies from western Europe (33%; p=0.37) [28,32].…”
Section: Incidence Of Acute Pancreatitis Across Europementioning
confidence: 94%
“…Studies that reported the highest ratios of gallstone to alcohol acute pancreatitis of more than six to one are solely from southern European Mediterranean countries, Greece [28], Turkey [33], and Italy [34,35], while studies with the lowest ratios of gallstone to alcohol aetiology of 9 less than 0.5 to one are mainly from eastern European countries, Hungary [28], Latvia [26], and Romania [25], along with Finland [31].…”
Section: Aetiology Of Acute Pancreatitis Across Europementioning
confidence: 99%
“…Thus, efficient management of SAP is very important. Evidence accumulated over the last years demonstrate that continuous venovenous hemofiltration (CVVH) is of benefit for SAP, because of its removal of inflammatory molecules (6–8). Particular attention has been paid to high‐volume hemofiltration (HVHF), which might be better (9).…”
mentioning
confidence: 99%